BRCA1 c.68_69delAG (exon2), c.181T>G (exon5), c.798_799delTT and 943ins10 (exon11) mutations in Burkina Faso - Abdou Azaque Zoure; Meriem Slaoui; Hierrhum Aboubacar Bambara; Alexis Yobi Sawadogo; Tegwendé Rebeca Compaoré; Nabonswindé Lamoussa Marie Ouédraogo; Mohammed El Mzibri; Mohammed Attaleb; Si Simon Traoré; Jacques Simpore; Youssef Bakri (AOSIS, 2018)
The worldwide variation of BRCA mutations is well known. The c.68_69delAG, c.181T>G, c.798_799delTT mutations in BRCA1 were observed in Moroccan, Algerian and Tunisian Breast Cancer families and were described founder mutation in Northern Africa. The 943ins10 is also recognized a founder mutation in West Africa. To our knowledge no study has been published on BRCA1/2 germline mutations and hereditary breast cancer (HBC) in population of Burkina Faso. The aim of the present study (first in Burkina Faso) was to screen for these four mutations in 15 unrelated patients with HBC. Mutation analysis was performed by Sanger sequencing of coding exon2, Exon5 and exon11A sequences of the BRCA1 gene. Blood specimens of 15 patients from Burkina Faso, with HBC were collected at the University Hospital Yalgado OUEDRAOGO( CHU-YO) of Ouagadougou in Burkina Faso. c.68_69delAG (exon2), c.181T>G (exon5), c.798_799delTT and 943ins10 (exon11) mutations were not detected in any of the 15 women diagnosed with family breast cancer history. Genetic analysis in this study, we show that targeting relevant exons in BRCA1 genes did not allow detection of mutations in the population of Burkina Faso. Therefore, such an approach may be of interest to perfom a complete sequencing of BRCA1 and BRCA2 genes in families at a high risk of developing breast cancer in Burkina Faso.